Inspired by Hummus

Calculus Level 5

0 1 { 1 x 1 / 6 } d x = A B π C D \int _{ 0 }^{ 1 }{ \left\{ \dfrac { 1 }{ { x }^{1/6 } } \right\} \,dx } =\dfrac { A }{ B } -\dfrac { { \pi }^{ C } }{ D }

The equation above holds true for positive integers A , B , C , A,B,C, and D D , with A A and B B coprime.

Find A + B + C + D A+B+C+D .

Notation : { } \{ \cdot \} denotes the fractional part function .


The answer is 962.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Hamza A
Apr 5, 2016

let's generalize this

0 1 { 1 x k } d x \displaystyle\int _{ 0 }^{ 1 }{ \left\{ \frac { 1 }{ \sqrt [ k ]{ x } } \right\} dx }

substituting x = 1 t k x=\frac { 1 }{ { t }^{ k } }

we get

k 1 { t } t k + 1 d t = k n = 1 n n + 1 t n t k + 1 d t k\displaystyle\int _{ 1 }^{ \infty }{ \frac { \{ t\} }{ { t }^{ k+1 } } dt } =k\displaystyle\sum _{ n=1 }^{ \infty }{ \int _{ n }^{ n+1 }{ \frac { t-n }{ { t }^{ k+1 } } }dt }

evaluating the integral and after simplifying a bit

k k 1 n = 1 ( 1 ( n + 1 ) k 1 1 n k 1 ) + n = 1 n ( 1 ( n + 1 ) k 1 n k ) = k k 1 + n = 1 ( 1 ( n + 1 ) k 1 1 n k 1 ) n = 1 1 ( n + 1 ) k = k k 1 ζ ( k ) \frac { k }{ k-1 } \displaystyle\sum _{ n=1 }^{ \infty }{ \left( \frac { 1 }{ (n+1)^{ k-1 } } -\frac { 1 }{ { n }^{ k-1 } } \right) } +\displaystyle\sum _{ n=1 }^{ \infty }{ n\left( \frac { 1 }{ (n+1)^{ k } } -\frac { 1 }{ { n }^{ k } } \right) } =\\ \frac { k }{ k-1 } +\displaystyle\sum _{ n=1 }^{ \infty }{ \left( \frac { 1 }{ (n+1)^{ k-1 } } -\frac { 1 }{ { n }^{ k-1 } } \right) } -\displaystyle\sum _{ n=1 }^{ \infty }{ \frac { 1 }{ (n+1)^{ k } } } =\frac { k }{ k-1 } -\zeta (k)

then we substitute k = 6 k=6

First Last
Apr 5, 2016

For simplicity, f ( x ) = 1 x 1 / 6 f(x) = \frac{1}{x^{1/6}}

0 1 { f ( x ) } d x = 0 1 f ( x ) d x f ( x ) d x \displaystyle\int_{0}^{1}\{f(x)\}dx = \displaystyle\int_{0}^{1}f(x)dx - \lfloor f(x) \rfloor dx

0 1 f ( x ) d x \displaystyle\int_{0}^{1}f(x)dx obviously is 6 5 \frac{6}{5}

0 1 f ( x ) d x \displaystyle\int_{0}^{1}\lfloor f(x) \rfloor dx is evaluated as

i = 1 i 6 ( i + 1 ) 6 i d x = ζ ( 6 ) = π 6 945 \displaystyle\sum_{i=1}^{\infty} \displaystyle\int_{i^{-6}}^{(i+1)^{-6}}idx = -\zeta(6) = \frac{-\pi^{6}}{945} as between each of these intervals f ( x ) = i \lfloor f(x) \rfloor = i

6 5 π 6 945 \boxed{\displaystyle\frac{6}{5}-\frac{\pi^6}{945}}

Nice method!

Aditya Kumar - 5 years, 2 months ago

Log in to reply

Thanks! :)

First Last - 5 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...